Numerical modeling of plasma-assisted combustion effects on firing and intermediates in the combustion process of methanol–air mixtures. (1st February 2020) - Gong, Changming; Yi, Lin; Wang, Kang; Huang, Kuo; Liu, Fenghua
Abstract: The effects of plasma-assisted ignition and combustion on the ignition-delay time ( T id ) and intermediates in methanol combustion were simulated numerically through a chemical-kinetics mechanism of methanol oxidation. Plasma-assisted ignition can considerably shorten the T id . Plasma-assisted ignition is more conducive to a low temperature and the lean combustion of a methanol-air mixture. According to the shortest T id, the active particle order is: O < CH3 O < 220 Td < H < OH < CH2 OH < CH3  < autoignition. The concentration of O atoms in active particles affects the T id shortening. Plasma-assisted combustion can significantly shorten the time for the system temperature to reach a maximum. The concentrations of the reactants CH3 OH and O2 decrease sharply for autoignition after the ignition-delay period, and the products CO, CO2 and H2 O increase rapidly. In plasma-assisted combustion, the addition of active particles significantly increases the rate of chemical reaction of consumption of O2, promotes the rapid redox reaction of methanol–air mixtures, oxidizes methanol fuel to CO2 and H2 O more rapidly, and accelerates combustion. The sensitivity coefficients of temperature and T id for plasma-assisted combustion are lower than those for autoignition. Highlights: Plasma-assisted combustion in methanol-air mixtures is numerical simulated. Plasma-assisted ignition can significantly shorten ignition delay time. The O atom plays a key role in shortening ignition delay time. The evolution mechanism of intermediates is clarified. Sensitivity coefficient for plasma-assisted combustion is lower than autoignition.